Building women’s climate resilience through smart groundnut socio-technical innovation bundle in Ghana - Obeng Adomaa, Faustina (2024)
Interventions aimed at building climate resilient communities require a mixture of instruments that speak to the peculiar realities of women, youth, and other vulnerable groups. Building of learnings from 2021-2023, this InfoNote presents a social technical innovation bundle for smart groundnut production that brings together technical solutions and institutional arrangements to address the primary challenges that women groundnut farmers in northern Ghana face. The Info Note also presents pathway for scaling this smart groundnut socio-technical innovation bundle.